Food insecurity in Burkina Faso (2000-2010) - Abdou Nassir, Bado (Kulliyyah of Islamic Reveled Knowledge and Human Sciences , International Islamic University Malaysia, 2013)
Burkina Faso and many other developing countries have suffered various security problems since independence. It is believed that armed conflicts, social instability and cross-border threats are the chief sources of danger the countries face. However, recently it is understood that many people in Burkina Faso and other countries encounter more threats posed by health, political, economic, food, environment, community, and personal insecurities than that of armed conflicts and cross-border vandalism. This study examines the state of food insecurity in Burkina Faso between 2000 to 2010 with regard to human security under the principle of “freedom from fear and freedom from want”. The study has hypothesized that chronic poverty, rapid population growth and poor infrastructure are the main reasons for food insecurity in Burkina Faso. Thus, a quantitative analytical approach has been used in the study to test the hypotheses and facilitate understanding of the issue. Though there are desires and initiatives to eradicate poverty and infrastructure shortage, the analyses show a strong correlation between the factors and the outcome. Moreover, the analysis of food insecurity indicators demonstrates that the country is food unsecured because of its poverty rate [46 percent], population growth ratio [3.2 percent] and infrastructure deficiency, among other issues. The results and recommendations of the study provide a platform to overcome the problem and create a sustainable human development in the country.